Metode Regresi Linier Berganda dan Cochrane-Orcutt untuk Menganalisis Daya Beli Masyarakat di Kabupaten Halmahera Utara - Puny, Yosses Rolan; Kahar, Arifin M.; Rizanto, Ilham A. R.; Lesnussa, Trifena P.; Kaseside, Meidy (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
Purchasing power parity, as measured by adjusted real per capita expenditure, is one of the essential indicators for evaluating the level of welfare within a community in a region. Several economic factors can influence the increase in purchasing power parity in an area, including local government spending, investment, and economic growth. By considering the current achievement of purchasing power parity and the relationship between the three economic factors with purchasing power parity, this study aims to determine the effect of local government spending, investment, and economic growth on the purchasing power parity in North Halmahera Regency for the period 2011-2024. To analyze these relationships, we used Multiple Linear Regression along with the Cochrane-Orcutt method to overcome the problem of autocorrelation assumption in the residuals. After conducting two iterations of the Cochrane-Orcutt method to develop a model with non-autocorrelation, the results show that the investment variable has a positive and significant effect on purchasing power parity. In contrast, local government spending and economic growth exhibit a negative and significant effect on purchasing power parity in North Halmahera Regency.